Exact and locally implicit source term solvers for multifluid-Maxwell systems - Wang, Liang; Hakim, Ammar H.; Ng, Jonathan; Dong, Chuanfei; Germaschewski, Kai (Journal of computational physics, 2020)
•A locally implicit algorithm is presented to efficiently update the source terms of a coupled multifluid-Maxwell system.•A direct computing algorithm is constructed to further improve performance substantially.•The model is successfully applied to complex, large systems.•An exact algorithm based on the analytic solution is also formulated. Recently, a family of models that couple multifluid systems to the full Maxwell equations have been used in laboratory, space, and astrophysical plasma modeling. These models are more complete descriptions of the plasma than reduced models like magnetohydrodynamic (MHD) since they are derived more closely from the full kinetic Vlasov-Maxwell system, without assumptions like quasi-neutrality, negligible electron mass, etc. Thus these models naturally retain non-ideal MHD effects like electron inertia, Hall term, pressure anisotropy/nongyrotropy, displacement current, among others. One obstacle to broader application of these models is that an explicit treatment of their source terms leads to the need to resolve rapid processes like plasma oscillation and electron cyclotron motion, even when these are not important. In this paper, we suggest two ways to address this issue. First, we derive the analytic solutions to the source update equations, which can be implemented as a practical, but less generic solver. We then develop a time-centered, locally implicit algorithm to update the source terms, allowing stepping over the fast kinetic time-scales. For a plasma with S species, the locally implicit algorithm involves inverting a local (3S+3)×(3S+3) matrix only, thus is very efficient. The performance can be further increased by using the direct update formulas to skip null calculations. We present benchmarks illustrating the exact energy-conservation of the locally implicit solver, as well as its efficiency and robustness for both small-scale, idealized problems and large-scale, complex systems. The locally implicit algorithm can be also easily extended to include other local sources, like collisions and ionization, which are difficult to solve analytically.